Collaborative Governance Dalam Program Arek Suroboyo Siap Kerjo (ASSiK) Sebagai Upaya Penyerapan Tenaga Kerja di Kota Surabaya - Prasetyo, Muhammad Alfian; Mulia Nanda, Adevansyah Wika; Suyatno, Ananda Nurhaliza; Pradika, Nurul Aini; Widiyarta, Agus (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
The Surabaya City Manpower Department (Disnaker) is collaborating with the private sector in implementing the Arek Suroboyo Ready to Work (ASSiK) program with the Collaborative Governance scheme. This collaboration aims to help increase opportunities for workers who have Surabaya ID cards, as well as making it easier for the private sector to recruit workers who match the company's criteria. This research aims to determine the process of Collaborative Governance in implementing the ASSiK program using Ansell & Gash's Collaborative Governance theory. The research method used in this research is qualitative with a descriptive approach. The results of this research show that five important indicators in the Collaborative Governance process between stakeholders, namely, face-to-face dialogue, building trust, commitment to the process, shared understanding, and intermediate outcome in implementing the ASSiK program have gone well and are in accordance with the initial objectives of the the existence of the ASSiK program.